Pengembangan Media Pembelajaran Roda Putar Rangsa Dalam Pembelajaran IPS Pada Siswa Kelas IV Sekolah Dasar - Masyithah, Almarhia; Hakim, Lukman; Aryaningrum , Kiki (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research is entitled Development of Rangsa Spin Wheel Media in Social Studies Learning for Class IV Elementary School Students. The aim of this research is to develop a product in the form of Rangsa spin wheel learning media in social studies learning for Class IV elementary school students. To determine the effectiveness and practicality of developing learning media. Rangsa spinning wheel in social studies learning for fourth grade elementary school students. This research adopts the Research and Development type of research using Analysis, Design, Development and Implementation. The results of this research are based on research conducted on the development of the Rangsa Spin Wheel Media with the help of the Canva Application in Social Sciences Subjects for Class V students of SDN 96 Palembang, it can be concluded that the media was developed using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model and was rated "Valid" based on evaluations from the four validators, with a validity percentage of 88% for the material aspect and 87%. % for other aspects. Individual and small group testing indicated that this medium was considered “Practical,” with percentages of 80% and 81% respectively. Teacher responses, which were evaluated through questionnaires, also showed a practicality level of 83%. Overall, the student learning test results showed an average score of 91.6% in the "Very Good" category. Keywords: Media Development, Learning, Rangsa Spin Wheel